Political ecology and environmentalism in Britain - Prendiville, Brendan; Haigron, David (Cambridge Scholars Publishing, 2020)
This collection of essays highlights the different dimensions of the contemporary British environmentalist movement from a multidisciplinary viewpoint. Beginning with an historical overview of the movement, the reader is then presented with an analysis of the politics of climate change from a political science perspective. This is followed by a sociological examination of climate change protesters and environmental activism among young people. The volume also includes an analysis of the ideological relationship between political ecology and the British Left, as well as a case study of environm.